DIGITAL INTERFACE IN HEALTH: ETHICAL DIMENSIONS OF TELEMEDICINE AND THE COMMUNICATION PERSPECTIVE - Eşidir, Osman Vedüd; Bak, Gökhan; Bak, Alparslan (Izmir Katip Celebi University, 2025)
The rapid advancement of information and communication technologies has made telemedicine a central component of modern healthcare. Initially developed to extend medical services to emergencies and remote regions, it has become institutionalized within health systems. The COVID-19 pandemic accelerated this process, transforming physician–patient interactions and raising questions about safeguarding ethical principles such as autonomy, privacy, justice, and beneficence–nonmaleficence in digital contexts. This study explores the ethical dimensions of telemedicine from a communication perspective, emphasizing the redefined boundaries of physician–patient relationships. It traces telemedicine’s evolution from early telegraph and telephone consultations to satellite-based systems and contemporary internet applications. The analysis focuses on communication dynamics widely experienced during the pandemic, including differences from face-to-face interaction, the challenge of sustaining empathy and trust online, and shifting power relations. Findings indicate that while telemedicine enhances accessibility and efficiency, it also creates risks of miscommunication, weaker emotional connection, and data security concerns. Moreover, inequalities in digital access deepen ethical debates about justice. The study concludes that empathy, trust, and transparency must be reconsidered, offering communication-based recommendations for sustaining ethical healthcare in the digital era.

Bilgi ve iletişim teknolojilerindeki hızlı gelişmeler, tele-tıbbı modern sağlık hizmetlerinin merkezi bir unsuru haline getirmiştir. Başlangıçta acil durumlar ve uzak bölgelerde sağlık hizmetine erişimi kolaylaştırmak amacıyla geliştirilen bu uygulamalar, zamanla sağlık sistemleri içinde kurumsallaşmıştır. COVID-19 pandemisi bu süreci hızlandırmış, hekim–hasta etkileşimlerini dönüştürmüş ve özerklik, mahremiyet, adalet ile yararlılık–zarar vermeme gibi etik ilkelerin dijital ortamlarda nasıl korunabileceği sorusunu gündeme getirmiştir. Bu çalışma, tele-tıbbın etik boyutlarını iletişim perspektifinden ele almakta ve dijital ortamlarda yeniden tanımlanan hekim–hasta ilişkilerinin sınırlarına odaklanmaktadır. Çalışma, telgraf ve telefon aracılığıyla yapılan ilk danışmalardan uydu destekli sistemlere ve günümüz internet tabanlı uygulamalarına kadar tele-tıbbın tarihsel gelişimini izlemektedir. Analiz, pandemi sürecinde yaygınlaşan uygulamalarda yüz yüze iletişimden farklılıkları, çevrim içi ortamda empati ve güvenin yeniden üretimindeki güçlükleri ve değişen güç dengelerini incelemektedir. Bulgular, tele-tıbbın erişim ve verimliliği artırmasına rağmen yanlış iletişim, zayıflayan duygusal bağ ve veri güvenliği gibi riskler yarattığını göstermektedir. Ayrıca dijital erişimdeki eşitsizlikler, adalet ilkesine dair etik tartışmaları derinleştirmektedir. Çalışma, empati, güven ve şeffaflığın yeniden değerlendirilmesi gerektiğini vurgulamakta ve dijital çağda etik sağlık hizmetlerinin sürdürülebilirliği için iletişim temelli öneriler sunmaktadır.
DİJİTAL ARA YÜZDE SAĞLIK: TELE-TIBBIN ETİK BOYUTLARI VE İLETİŞİM PERSPEKTİFİ
Keywords: Communication Studies; İletişim Çalışmaları; Communication and Media Studies (Other); İletişim ve Medya Çalışmaları (Diğer)